Concentrating solar power plants for electricity and desalinated water production - Kalogirou, Soteris A. (My University, 2011)
Electricity and water are two commodities which are usually both required in arid countries having a high solar insolation. A number of technologies exists for both systems, which are briefly reviewed in this paper. Among the most matured and suitable concentrated solar power (CSP) plants for electricity generation are the solar tower (ST) and the parabolic trough collector (PTC) systems, whereas for desalination these are the multiple effects distillation (MED) type evaporator and the reverse osmosis (RO). The paper shows also the possibilities that exist and the ways that these technologies can be combined in order to produce simultaneously electricity and water. The equipment required to be used for these systems (steam cycle components, MED or RO) is usually very expensive therefore, the system is required to operate continuously without complete shut down during the night. Such a system would be very suitable for arid countries, which due to the water shortage problem they face, locate power plants in coastal areas in order to use the seawater for the cooling needs of the steam cycle system (condenser). Therefore, in this case it would be comparatively easy to combine the power system with desalination as the resource for such a system, i.e., seawater would be readily available.
Keywords: Parabolic trough collectors; Power tower; Multiple effect boiling; Reverse osmosis; Desalination